Modified vector method of anti-interference encoding; Izvestiya Akademii Nauk UzSSR; № 2 - Ivin V. A. (1990, 1990)
A modification of the vector method of anti-interference encoding is proposed: it allows all errors in received data to be detected, and allows correction of two-bit errors and a number of multi-bit errors. The principle and a design algorithm of the optimum system for three encoding vectors are given.